2017
DOI: 10.1111/bcpt.12717
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Effect Profile of Topical Ocular Administration of Fingolimod for Treatment of Dry Eye Disease

Abstract: Fingolimod is a promising prodrug in attenuating multiple sclerosis and prolonging survival of organ allograft, with many other protective effects. Its mechanism of action is related to the internalization of sphingosine 1-phosphate receptors (S1PRs). Our previous study indicated that fingolimod eyedrops was efficacious in inhibiting ocular inflammation in a dry eye disease (DED) model of non-obese diabetic (NOD) mice. In the current study, we evaluated potential adverse effects of fingolimod eyedrops. Inbred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…It is also reported that cationic emulsion of cyclosporine A is very efficient in the management of corneal epithelium lesion [Daull et al, 2016]. Fingolimod is a systemic drug in the management of multiple sclerosis, suggested for controlling dry eye disease as well [Xiao et al, 2016]. Fingolimod is a systemic drug in the management of multiple sclerosis, suggested for controlling dry eye disease as well [Xiao et al, 2016].…”
Section: Management Of Delayed Ocular Complications Medical Managementsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is also reported that cationic emulsion of cyclosporine A is very efficient in the management of corneal epithelium lesion [Daull et al, 2016]. Fingolimod is a systemic drug in the management of multiple sclerosis, suggested for controlling dry eye disease as well [Xiao et al, 2016]. Fingolimod is a systemic drug in the management of multiple sclerosis, suggested for controlling dry eye disease as well [Xiao et al, 2016].…”
Section: Management Of Delayed Ocular Complications Medical Managementsmentioning
confidence: 99%
“…Tacrolimus has been described as an effective drug in the treatment of keratoconjunctivitis, controlling the inflammation in ocular tissues, and improving the tear film stability [Moscovici et al, 2015;Chatterjee and Agrawal, 2016]. Fingolimod is a systemic drug in the management of multiple sclerosis, suggested for controlling dry eye disease as well [Xiao et al, 2016]. The safe concentrations of this drug are reported to be 0.005% and 0.1% based on a study on mice [Xiao et al, 2016].…”
Section: Management Of Delayed Ocular Complications Medical Managementsmentioning
confidence: 99%
See 1 more Smart Citation
“…This novel formulation may be a long-term therapeutic alternative. 86 In SM-exposed patients, dry eye treatment is vital for reducing ocular symptoms and enhancing quality of life.…”
Section: Anti-inflammatory Drugsmentioning
confidence: 99%
“…17 Moreover, both our pharmacology and toxicology studies indicated that a range of 0.005% to 0.1% fingolimod is preferable as a formulation of eye drop applied in ocular surface. 17,18 These beneficial effects of fingolimod in DED are interesting and encouraging. However, the detailed mechanisms remain unknown.…”
mentioning
confidence: 94%